Influence of mining ground fissures development on seedling bank and seedling establishment factors in semi-arid mining area - Huadong DU; Shanshan XIE; Yinli BI; Yan LIU; Hao SUN; Yunlong LIU (Meitan kexue jishu, 2024)
In semi-arid areas, underground coal mining could cause ecological and environmental problems such as surface subsidence, which can increase soil erosion intensity and damage vegetation habitats. In these ecological damages, the effect of mining ground fissures development on the seedling banks still needs to be studied further for its important role in plant restoration. In this study, the density, composition, and diversity characteristics of seedling banks were clarified at different horizontal distances (0-1 m, 1-2 m, and 2-5 m) from the mining ground fissuresin the Yushenfu mining area. Then the spatial variability of driving factors affecting seedling establishment were explored by combining soil factors, aboveground vegetation communities and litters characterization. Finally, the species similarity model was used to explore the effects of seedling banks on the natural vegetation regeneration in different areas from the ground fissures. The results showed that: ① In the control site without fissures development, the composition of the seedling bank was dominated by perennial grasses (57%), but after fissures development, the proportion of perennial herbs decreased to 30% and 35% in the 0-1 m and 1-2 m area from the fissures, respectively. Compared with the control sites, the seedling density increased significantly by 92% and 68% in 0-1 m and 1-2 m area, the Margalef richness index, Shannon-Wiener diversity index, and Simpson dominance index of the seedling bank increased by 42% and 24%, 62% and 40%, and 33% and 18%, but Pielou evenness index was reduced by 55% and 38%, respectively. However, there were no significant differences in the composition, density and diversity of seedling bank in 2-5 m area from the ground fissures compared to the control area. Therefore, the impact of ground fissures development on the characteristics of the seedling bank was within the range of 2 meters. ② After the development of ground fissures, the same factors affected seedling establishment were soil moisture content, soil organic matter content and litter thickness in the 0-1 m and 1-2 m areas from the ground fissures. In addition to the above factors, seedling establishing factors in 0-1 m area also included litter cover, soil crust cover and thickness, aboveground vegetation cover and biomass. With increasing distance from ground fissures, the key factors limiting seedling establishment were reduced in the 2-5 m area, and were similar to those in the control area, which included soil moisture content, aboveground vegetation cover, and litter cover. ③ In 0-1 m and1-2 m areas from ground fissures, the annual herbaceous species composition were less similar to that of above-ground vegetation species which dominated by the perennial herbs, the species similarity is only 0.42 and 0.48, respectively. Considering the weak contribution of annuals to plant community succession, it can be concluded that the contribution of the seedling bank is limited for vegetation restoration with in the 0-2 m areas from the ground fissures which is greatly disturbed by the fissure. In the 2-5 m area and control area, the species similarity between the seedling bank and aboveground vegetation was 0.67 and 0.68, which indicate that the recovery potential of the vegetation community is not affected by the development of ground fissures in this area.